(untitled) (Journal of Social Sciences Review, 2023)
This abstract aims to explore the vital connection between marketing ethics and clients’ satisfaction. Ethics in marketing refers to the moral principles and values that guide marketers in their decision-making processes and interactions with clients. One of the fundamental aspects of marketing ethics is the truthful and accurate representation of products or services. Misleading or deceptive marketing practices erode clients’ trust and can lead to dissatisfaction. Additionally, marketers need to respect clients’ privacy and handle their personal information with utmost care. Ethical data collection and usage practices not only protect clients’ privacy rights but also contribute to their satisfaction. Moreover, corporate social responsibility (CSR) plays a vital role in marketing ethics. Clients are increasingly concerned about the social and environmental impact of the organizations they engage with. Ethical marketing involves incorporating CSR initiatives into business strategies, addressing societal concerns, and demonstrating a commitment to sustainability. In conclusion, marketing ethics significantly influence clients’ satisfaction by fostering trust, transparency, and fairness. Adhering to ethical principles in marketing ensures accurate product representation, respect for privacy, avoidance of manipulative tactics, and incorporation of CSR initiatives. Organizations that prioritize marketing ethics not only enhance clients’ satisfaction but also establish long-term relationships, resulting in sustainable business growth.